Analysis of the Impact of Company Merger on Company Financial Performance: A Case Study of PT Perikanan Indonesia - Carla Theresia, Yohana; Damayanti, Prisilla; Dwiyani Hadiwidjaja, Rini (DINASTI RESEARCH, 2025)
This study aims to analyze the impact of the merger between PT Perikanan Indonesia and PT Perikanan Nusantara on the financial performance of the merged entity. This merger was implemented in 2021 as an effort to improve operational efficiency and company competitiveness. The research data includes PT Perikanan Indonesia's financial statements over a six-year period, namely three years before and three years after the merger (2018–2023). The research method used is quantitative, with analysis techniques including descriptive statistics, the Kolmogorov-Smirnov normality test, and the Wilcoxon Signed Rank Test. The analysis results show that liquidity ratios (CR and QR) decreased, while solvency ratios (DAR and DER) increased. On the other hand, profitability ratios (NPM, ROA, ROE) showed a downward trend after the merger. These findings indicate that the merger did not have a positive impact on PT Perikanan Indonesia's financial performance, caused by increased liabilities and a less than optimal integration process. The implications of this study highlight the need for more mature and flexible post-merger integration strategy planning.